Building Microservices with ASP.NET Core : develop, test, and deploy cross-platform services in the cloud - Hoffman, Kevin (O'Reilly Media, Inc., 2017)
Chapter 7. Building an ASP.NET Core Web Application; ASP.NET Core Basics; Adding ASP.NET MVC Middleware; Adding a Controller; Adding a Model; Adding a View; Invoking REST APIs from JavaScript; Building Cloud-Native Web Applications; API First; Configuration; Logging; Session State; Data Protection; Backing Services; Environment Parity; Port Binding; Telemetry; Authentication and Authorization; Summary; Chapter 8. Service Discovery; Refresher on Cloud-Native Factors; External Configuration; Backing Services; Introducing Netflix Eureka; Discovering and Advertising ASP.NET Core Services